Cost-effectiveness of sorafenib versus SBRT for unresectable advanced hepatocellular carcinoma. Issue 1 (December 2016) - Leung, Henry; Liu, Chung-Feng; Chan, Agnes
Abstract Objective Stereotactic body radiotherapy (SBRT) has been shown to improve overall survival in patients with advanced hepatocellular carcinoma. This study aimed to assess the cost-effectiveness of SBRT compared to sorafenib which is the only drug for advanced hepatocellular carcinoma. Methods A Markov decision-analytic model was performed to compare the cost-effectiveness of SBRT and sorafenib for unresectable advanced hepatocellular carcinoma. Patients transitioned between three health states: stable disease, progression disease and death. We calculated the data on cost from the perspective of our National Health Insurance Bureau. Sensitivity analyses were conducted to determine the impact of several variables. Results The incremental cost effectiveness ratio (ICER) for sorafenib compared to SBRT was NT$3, 788, 238 per quality-adjusted life year gained (cost/QALY), which was higher than the willingness to pay threshold of Taiwan according to WHO's guideline. One-way sensitivity analysis revealed that the utility of progression disease for the sorafenib treatment, utility of progression free survival for SBRT, utility of progression free survival for sorafenib, utility of PFS to progression disease for SBRT and transition probability of progression disease to dead for SBRT were the most sensitive parameters in all cost scenarios. The Monte-Carlo simulation demonstrated that the probability of cost-effectiveness at a willingness to pay threshold of NT$ 2, 213, 145 per QALY was 100 % and 0 % chance for SBRT and sorafenib. Conclusion This study indicated that SBRT for advanced hepatocellular carcinoma is cost-effective at a willingness to pay threshold as defined by WHO guideline in Taiwan.